Effects of Instructional Analogy (IA) and Lecture Method (LM) On Basic Science (BS) Students’ Achievement and Attitude in Delta Central Senatorial District (DCSD). (Journal of Universal Science Research, 2023)
IA and LM’s effects on achievement and attitude of students to BS in DCSD were investigated using 3x2 factorial quasition experimental design. The population was 12,163 JSII Public Secondary schools’ students in DCSD. 214 JSII Basic Science students in six intact classes participated in the study. Experts validated Basic Science Achievement Test (BSAT) and Basic Science Attitude Scale (BSAS) were used for the collection of data. BSAT and BSAS had 0.88 and 0.78 reliability coefficients. Analysis of Covariance was used to analyse the data that were acquired. The findings revealed a substantial difference in favour of IA between the mean achievement and attitude ratings of students who were taught BS using IA and LM. The study came to the conclusion that IA improves students' performance and attitude toward BS more than LM. It was recommended that BS teachers should use IA when instructing BS at the junior secondary level, among other things.